2016
DOI: 10.4103/1735-9066.193414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reproductive health indicators in women affected by East Azarbaijan earthquake on August 2012

Abstract: Background:Ignoring reproductive health services during natural disasters leads to some negative consequences such as reduced access to contraceptive methods, sexual disorders, and pregnancy complications. Despite previous researches, there is still more need for research on this area of health. This study attempts to identify the indicators of reproductive health in the women affected by the East Azarbaijan earthquake on August 2012.Materials and Methods:In this descriptive study, reproductive health informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…There is no study examining the direct and indirect effect of earthquake experiences on birth weight simultaneously to compare our findings. However, the findings of our study are in line with the findings of audits of hospital records that babies born after earthquakes had lower birthweight compared to those who born before the earthquakes [ 16 , 18 21 ] and indicate that experiencing an earthquake while pregnant can adversely affect birth outcomes. Further, our study findings are in line with previous investigations of the relationship between antenatal CMDs and baby birthweight in general circumstances, which have found a significant negative association [ 6 , 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…There is no study examining the direct and indirect effect of earthquake experiences on birth weight simultaneously to compare our findings. However, the findings of our study are in line with the findings of audits of hospital records that babies born after earthquakes had lower birthweight compared to those who born before the earthquakes [ 16 , 18 21 ] and indicate that experiencing an earthquake while pregnant can adversely affect birth outcomes. Further, our study findings are in line with previous investigations of the relationship between antenatal CMDs and baby birthweight in general circumstances, which have found a significant negative association [ 6 , 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…Daha önceki depremlerde kadınlara ve kız çocuklarında şiddet ve cinsel istismarın arttığı belirtilmiştir (Tearne et al 2021). Afet sonrasında çocuğu olan kadınların artan sorumluluk ve bakım yükleri, toplumun kadına atfettiği annellik rolü gibi nedenler yaşanan stresi artırıp ruh sağlığını olumsuz etkilemektedir (Bahmanjanbeh et al 2016;Calayır ve Aker, 2021ve Çelik Or, 2019.…”
Section: Ruhsal Etkilerunclassified
“…A study of women affected by the Fukushima earthquake and nuclear disaster found that discontinuation of scheduled PNC or switching to another medical institution for PNC was associated with a reduced likelihood of breastfeeding [ 15 ]. Caesarean section rates were found to be higher after Hurricane Katrina [ 5 ] and after an earthquake in Azerbaijan [ 16 ]. PNC also has benefits beyond the strictly medical.…”
Section: Introductionmentioning
confidence: 99%